Sejarah, Perkembangan dan Revolusi Pertanian Dalam Tamadun Islam serta Kaitannya Dengan Zaman Moden : History, Development and Revolution of Agriculture in Islamic Civilization and Their Relevance to Modern Times - Ismil, Raihan; Baharuddin, Madiha; Mohd Lutfi, Siti Solehah (Journal of Al-Tamaddun, 2024)
Islamic civilization witnessed an extraordinary agricultural revolution that played an important role in shaping the socio-economic landscape. The aim of this abstract is to provide an overview of this revolution, exploring the main drivers, impacts, and changes that occurred. This research was carried out using qualitative method. This method involves a library study which is a comprehensive literature review about the agricultural revolution in Islamic civilization and its connection with modern times. The agricultural revolution in Islamic civilization emerged during the Islamic Golden Age (8th to 14th centuries), characterized by advances in various fields of knowledge, including agriculture. One of the main factors behind this agricultural revolution was the development and spread of new cultivation systems. This system not only increases agricultural productivity but also facilitates the expansion of cultivated areas in arid and semi-arid areas. Islamic agricultural practices also produced Islamic scientists such as Ibn al-Awwam who studied plants, soil fertility, and agronomy, which led to the introduction of new plant varieties and better planting techniques. Their scientific discoveries and experiments laid the foundation for modern agricultural science. In addition, the connection of the agricultural revolution in Islamic civilization with modern agriculture lies in its sustainable and efficient techniques. Emphasis on irrigation management, crop conservation, and the use of technology in line with approaches such as precision agriculture, conservation agriculture, and sustainable farming methods. In conclusion, the agricultural revolution in Islamic civilization has a great connection with modern agriculture. By taking the lessons of the Islamic agricultural revolution, we can strive to improve management in cultivation, technological innovation, and increase production in our efforts to create a resilient and productive agricultural system for the future.